Proceedings of the 41st International Conference on Advanced Ceramics and Composites. a collection of papers presented at the 41st International Conference on Advanced Ceramics and Composites January 22-27, 2017, Daytona Beach, Florida - Kriven, Waltraud M.; Bansal, Narottam P.; Kusnezoff, Mihails; Ohji, T. (Tatsuki); Zhou, Yanchun; Il Moon, Kyoung; Matyáš, Josef; Shimamura, Kiyoshi; Kirihara, Soshu; Gupta, Surojit; Wang, Jingyang (Materials scientist) (Wiley, 2018)
This proceedings contains a collection of 23 papers from The American Ceramic Society s 41st International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 22-27, 2017. This issue includes papers presented in the following symposia: Symposium 1 Mechanical Behavior and Performance of Ceramics and Composites Symposium 2 Advanced Ceramic Coatings for Structural, Environmental, and Functional Applications Symposium 4 Armor Ceramics: Challenges and New Developments Symposium 5 Next Generation Bioceramics and Biocomposites 6th Global Young Investigators Forum.